Psychological features of adolescents with essential hypertension - A. S. Kosovtseva (Scientific Сentre for Family Health and Human Reproduction Problems, 2018)
Background. The inconsistency of data about psychological profile of adolescents with essential arterial hypertension (EH), as one of the most important factor in the pathogenesis of this disease, causes the relevance of searching the relationship between psychological traits and features of the circadian blood pressure (BP).organization. The aim of this study was to study the association between personality characteristics and parameters of 24-hour blood pressure monitoring in adolescents with EH. Materials and methods. We carried out an investigation of 14-17 year old (15.92 ± 1.12) Caucasian male patients with EAH (n = 110) in clinic Scientific Centre for Family Health and Human Reproduction Problems. Psychological testing and ambulatory blood pressure monitoring (ABPM) have been carried. Results. In our study were determined some most significant psychological features which associated with different ABPM parameters and EH stabilization. Increased hypertension, manifested in excessive activity, irritability, anger and intractability, is associated with the stabilization of EH in adolescents. The ability to express emotions verbally or physically (including a constructive way) protects the cardiovascular system from excessive fluctuations of night blood pressure. Psychological profile with the leading pattern of anxiety-aggressive affect suppression (irritation, touchiness, anxiety, introversion) mainly influence to the time of hypertension and average daily level of blood pressure. Conclusion. Adolescents with EH with certain emotional and personal characteristics need to be treated by the differentiated psychotherapeutic interventions. These conditions are necessary for early prevention of complications of cardiovascular circadian organization disorders.